2019
DOI: 10.1016/j.idcr.2019.e00657
|View full text |Cite
|
Sign up to set email alerts
|

Native valve infective endocarditis due to Micrococcus luteus in a non-Hodgkin’s lymphoma patient

Abstract: Micrococcus species are typically considered contaminants from skin and mucous membranes. However, especially in severely immunocompromised patients, a blood culture with Micrococcus could be the cause of a significant infection. We report a 65-year-old female with non-Hodgkin’s lymphoma who developed native valve infective endocarditis due to Micrococcus luteus. There is no defined therapeutic regimen for infective endocarditis due to Micrococcus luteus; however, our patient was successfully treated for six w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The widespread occurrence, and also high variability in terms of copy number and composition of the potential VF and AR genes among M. luteus strains, emphasized their importance in the pathogenic features. It has been reported that M. luteus could cause severe infections in immunocompromised populations, including peritonitis, brain abscesses, pneumonia, septic arthritis and so on [21][22][23][24]. The presence of several virulence determinants and antibiotic-resistance genes in M. luteus should be paid attention to, the pro les of which will provide guidance for the future treatment of M. luteus infections.…”
Section: Potential Virulence Factors and Antibiotic Resistance Genes mentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread occurrence, and also high variability in terms of copy number and composition of the potential VF and AR genes among M. luteus strains, emphasized their importance in the pathogenic features. It has been reported that M. luteus could cause severe infections in immunocompromised populations, including peritonitis, brain abscesses, pneumonia, septic arthritis and so on [21][22][23][24]. The presence of several virulence determinants and antibiotic-resistance genes in M. luteus should be paid attention to, the pro les of which will provide guidance for the future treatment of M. luteus infections.…”
Section: Potential Virulence Factors and Antibiotic Resistance Genes mentioning
confidence: 99%
“…The rst documented disease caused by M. luteus was septic shock in 1978 [20]. In fact, M. luteus was once considered to be a non-pathogenic saprophyte or pure contaminant from skin and mucous membranes, but it is now proved to cause bacteremia, pneumonia, endocarditis, lymphoma, septic arthritis and any other diseases [21][22][23][24]. Therefore, as an important material of biotechnological interest and an emerging nosocomial pathogen, M. luteus has received increasing attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Coagulase-negative staphylococci and Micrococcus spp. are related to opportunistic infections, including community-acquired ones in immunocompromised subjects ( Seng et al 2017 ; Shi et al 2017 ; Ianiello et al 2019 ). In addition, strains B1N2 and DM4S1 were identified as S. aureus , a well-known pathogen responsible for a broad range of infections but particularly famous for causing food poisoning ( Sergelidis and Angelidis 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Micrococcus luteus, the type species of the genus Micrococcus (family Micrococcaceae, order Micrococcales), is a high GC Gram-positive cocci of the phylum Actinobacteria [1]. M. luteus is known as an opportunistic pathogen for nosocomial infections [2], and has been proved to be able to cause bacteremia, pneumonia, endocarditis, lymphoma, septic arthritis and many other diseases [3][4][5]. Besides as a pathogen, M. luteus is ubiquitously distributed in variety of habitats, including soil, air, marine, plant and the human body [6], indicating that this species has been well adapted to various environments.…”
Section: Introductionmentioning
confidence: 99%